Effect of density and Z-contrast on the visibility of noble gas precipitates and voids with insights from Monte-Carlo simulations. (November 2019) - Mir, Anamul H.; Hinks, Jonathan A.; Donnelly, Stephen E.
Highlights: Noble gases implanted into glasses precipitate as supercritical fluid inclusions. The precipitates of Xe and Kr can be unambiguously differentiated from voids. The precipitates under ion irradiation transform into voids which shrink and eventually close. Abstract: In this work, a detailed analysis of He, Ne, Ar, Kr and Xe precipitates in a complex borosilicate glass using transmission electron microscopy (TEM) with in-situ ion implantation is presented. With in-situ monitoring, the real-time dynamics of precipitate and void evolution under ion implantation was followed. Using appropriate equations of state and, Monte-Carlo simulations to supplement the TEM images, we then discuss in detail the possibility and ways of differentiating the precipitates of various noble gases from empty voids. It is shown that all the noble gases precipitate as inclusions of supercritical fluid. With the aid of the simulations, the crucial role played by the size and density of the precipitates and atomic number of the gas atoms in affecting the visibility of the precipitates is highlighted. The results show that the precipitates and voids can be unambiguously differentiated in the case of Xe and Kr whereas the precipitates of other lighter noble gases cannot be differentiated from the voids. However, the precipitate and void evolution under ion irradiation follow different dynamics, knowledge of which allows one to differentiate between the precipitates and voids even for lighter noble gases. Besides shedding light on the subject of noble gas precipitation and identification of the precipitates and voids, the study highlights the complexity in dissociating the behaviour of voids from the process of precipitate re-solution. This type of knowledge is pivotal in developing models describing the evolution of precipitates, voids and macroscopic porosity in a number of materials.